2017
DOI: 10.1002/2017gl072703
|View full text |Cite
|
Sign up to set email alerts
|

MMS observations of whistler waves in electron diffusion region

Abstract: Whistler waves that can produce anomalous resistivity by affecting electrons' motion have been suggested as one of the mechanisms responsible for magnetic reconnection in the electron diffusion region (EDR). Such type of waves, however, has rarely been observed inside the EDR so far. In this study, we report such an observation by Magnetospheric Multiscale (MMS) mission. We find large‐amplitude whistler waves propagating away from the X line with a very small wave‐normal angle. These waves are probably generat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
82
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 95 publications
(87 citation statements)
references
References 58 publications
2
82
0
Order By: Relevance
“…The bidirectional streaming is also consistent with being near the source region. Cao et al () also reported whistler waves streaming away from the EDR using MMS under similar conditions. In both cases, the whistler waves are in the exhaust and separatrix regions.…”
Section: The 22 October 2016 Edr Eventmentioning
confidence: 73%
“…The bidirectional streaming is also consistent with being near the source region. Cao et al () also reported whistler waves streaming away from the EDR using MMS under similar conditions. In both cases, the whistler waves are in the exhaust and separatrix regions.…”
Section: The 22 October 2016 Edr Eventmentioning
confidence: 73%
“…Whistler waves were also observed at the magnetopause near or inside the EDR propagating away from the X line (Cao et al, ; Tang et al, ). High‐resolution MMS observations showed that the resonance energy for anisotropic electron population inside EDR was ∼300 eV with maximum growth rate at f =0.2 f ce (Cao et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, our study showed the occurrence of a small number of whistler waves in the vicinity of X ‐line (see Figure b). Note also that Tang et al [] and Cao et al [] showed evidence of whistler waves in the electron diffusion region using the Time History of Events and Macroscale Interactions during Substorms and MMS measurements. Actually we cannot identify the electron diffusion using the limited time resolution of the Cluster data in present study.…”
Section: Discussionmentioning
confidence: 99%